On Certain Properties for Two Classes of Generalized Convex Functions - Mohamed S. S. Ali (Abstract and Applied Analysis)
Two classes of generalized convex functions in the sense of Beckenbach are considered. For both classes, we show that the existence of support curves implies their generalized convexity and obtain an extremum property of these functions. Furthermore, we establish Hadamard’s inequality for them.